2016
DOI: 10.3136/fstr.22.219
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Total Anthocyanin Content, Composition of Anthocyanidin, Total Phenolic Content and Antioxidant Activity of Pigmented Potato Peel and Flesh

Abstract: While fresh potato consumption is decreasing in many countries, more potatoes are processed into value-added products to meet the demand especially from the fast food and convenience food industries (Schieber and Saldana, 2009). Therefore, potato peels, as by-products from potato processing, represent a serious disposal problem to industry as well as environment and sustainability (Schieber and Saldana, 2009). However, potato peels contain lots of nutritional and functional compounds such as dietary fibers (La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…Reports have shown that the coloured potato peel contains many phenolic compounds, such as anthocyanins, phenolic acids and others . However, there have been no data on the proximate and mineral composition in the flesh and peel of red‐ and purple‐fleshed potatoes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that the coloured potato peel contains many phenolic compounds, such as anthocyanins, phenolic acids and others . However, there have been no data on the proximate and mineral composition in the flesh and peel of red‐ and purple‐fleshed potatoes.…”
Section: Introductionmentioning
confidence: 99%
“…19 Reports have shown that the coloured potato peel contains many phenolic compounds, such as anthocyanins, phenolic acids and others. 20,21 However, there have been no data on the proximate and mineral composition in the flesh and peel of red-and purple-fleshed potatoes. Therefore, the purpose of the present study was to evaluate and compare the proximate and mineral composition in the flesh and peels of six coloured potato cultivars grown in Lithuania.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the deep-purple color of potato flesh and skin is associated with the presence of petunidin derivatives, although studies on metabolite profiling revealed a genotype-and tissue-specific pattern regarding the anthocyanin composition [22]. Petunidin was the major anthocyanidin compound found both in the flesh and the peel of purple potato varieties studied by Yine et al [21]. In this study, petunidin accounted for 63-66% of the total anthocyanidin content of purple peel and flesh.…”
Section: Potatomentioning
confidence: 50%
“…Kita et al [23] found pelargonidin-3-p-coumaroylrutinoside-5-glucoside as the major anthocyanin present in red-fleshed varieties, such as Rosalinde (15.14 ± 0.12 mg·100 g −1 dw), Herbie 26 (44.46 ± 0.23 mg·100 g −1 dw), and Highland Burgundy Red (126.38 ± 0.71 mg·100 g −1 dw). Yin et al [21] carried out an acid hydrolysis of the anthocyanins, studying the composition of the aglycones (anthocyanidins), reporting pelargonidin as the main anthocyanidin present in the red-fleshed cultivar Red Cloud No. 1, with a concentration of 11.73 ± 0.16 mg·100 g −1 fresh weight (fw), which corresponded to 82% of the total anthocyanidin content.…”
Section: Potatomentioning
confidence: 99%
See 1 more Smart Citation